Rare growth pattern of a solitary cystic lung metastasis from colon cancer: a case report. Issue 8 (21st August 2019) - Eguchi, Keisuke; Nakajima, Takahiro; Terashima, Takeshi; Sasaki, Aya; Hasegawa, Hirotoshi; Matsui, Junichi
Abstract : An 82‐year‐old male, who had undergone sigmoid colon cancer surgery (at the age of 78 years) and primary lung cancer surgery (at the age of 81 years), was found to have a cavitating lesion in the left lower lobe on chest computed tomography (CT). A chest CT that had been performed just before the primary lung cancer surgery revealed a small thin‐walled cyst at the same site at which the cavity was detected in the current CT. Bronchoscopic examination revealed no evidence of malignancy. A follow‐up chest CT performed 5 months later revealed that the lesion had grown and that the cyst contained a well‐defined lobular nodule. Video‐assisted thoracoscopic left basal segmentectomy was performed. The histopathological diagnosis was metastasis from colon cancer. We report this unusual case in which a pulmonary metastasis changed over time from a cystic lesion to a nodular lesion. Abstract : We report a surgical case of a solitary pulmonary metastasis in which the lesion grew from a cyst into a nodular lesion within the cyst with time.